Singing Voice Melody Detection - Michael, Chourdakis (Transactions on Engineering and Computing Sciences, 2024)
This is an enhancement on our time domain pitch detection algorithm optimized for voice singing. Various time and frequency domain methods have been researched to detect the pitch of the human voice. This manuscript describes our methods to convert human singing to music notation. Over the past years, significant progress is made in speech recognition, but methods used in that process recognize textural patterns, not melody. We use a combination of time and frequency domain algorithms to achieve our aim using C++. The results of our algorithms are satisfactory and accurate enough, not only to represent human voice singing in the European notation, but also to represent it when higher resolution script is available - for example, when using the Byzantine Script which has a minimum note distance of about 17 Cents (as opposed to the European notation with a minimum note distance of 100 Cents).